A phase III study comparing SB3 (a proposed trastuzumab biosimilar) and trastuzumab reference product in HER2-positive early breast cancer treated with neoadjuvant-adjuvant treatment: Final safety, immunogenicity and survival results. (April 2018) - Pivot, X.; Bondarenko, I.; Nowecki, Z.; Dvorkin, M.; Trishkina, E.; Ahn, J.-H.; Im, S.-A.; Sarosiek, T.; Chatterjee, S.; Wojtukiewicz, M.Z.; Shparyk, Y.; Moiseyenko, V.; et al.
Abstract: Background: The equivalent efficacy between SB3, a proposed trastuzumab biosimilar, and the trastuzumab reference product (TRZ) in terms of the breast pathologic complete response rate after neoadjuvant therapy in patients with early or locally advanced human epidermal growth factor receptor 2-positive breast cancer was demonstrated in the previous report. Here, we report the final safety, immunogenicity and survival results after neoadjuvant-adjuvant treatment. Patients and methods: Patients were randomised 1:1 to receive neoadjuvant SB3 or TRZ for 8 cycles concurrently with chemotherapy (4 cycles of docetaxel followed by 4 cycles of 5-fluorouracil/epirubicin/cyclophosphamide). Patients then underwent surgery, followed by 10 cycles of adjuvant SB3 or TRZ as randomised. End-points included safety, immunogenicity, event-free survival (EFS) and overall survival through the adjuvant period. Results: Of 875 patients randomised, 764 (SB3, n = 380; TRZ, n = 384) completed the study. The median follow-up duration was 437 days in the SB3 group and 438 days in the TRZ group. The incidence of treatment-emergent adverse events was comparable between groups (SB3, 97.5%; TRZ, 96.1%) during the overall study period. Up to the end of study, the overall incidence of antidrug antibody was low in both treatment groups (3 patients each). EFS was comparable between groups with a hazard ratio (SB3/TRZ) of 0.94 (95% confidence interval, 0.59–1.51) and EFS rates at 12 months of 93.7% for SB3 and 93.4% for TRZ. Conclusions: Final safety, immunogenicity and survival results of this study further support the biosimilarity established between SB3 and TRZ. Trial registration: ClinicalTrials.gov (NCT02149524 );EudraCT (2013-004172-35 ). Highlights: Equivalent efficacy between SB3 and Herceptin ® in terms of the breast pathologic complete response rate was established. Event-free survival and overall survival results further support the biosimilarity established between SB3 and Herceptin ® . Safety and immunogenicity results were highly comparable with no clinically relevant differences between SB3 and Herceptin ® .